A multifactorial investigation of captive chimpanzees' intraspecific gestural laterality. (June 2016) - Prieur, Jacques; Pika, Simone; Barbu, Stéphanie; Blois-Heulin, Catherine
Abstract : Social laterality is the core of two major theories: one concerns the evolution of laterality at the population level and the other the evolution of human language. However, few studies have investigated gestural laterality in communication between conspecifics. To our knowledge, the present study is the first to investigate the production of intraspecific gestures taking into account the influence of multiple factors on gestural laterality: first, gestural characteristics (sensory modality, use of a communication tool, sharing degree in the population and duration); second, the interactional context (visual field and body sides of signaller and recipient, and emotional context); and third, individual sociodemographic characteristics of signaller and recipient (age, sex, group, hierarchy, affiliation and kinship). We questioned, first, whether gestural laterality differed with gesture at the population level and second, whether some factors influenced gestural laterality. To do so, we evaluated social laterality in dyadic interactions in 39 chimpanzees, Pan troglodytes, living in three groups in captivity. We found that, at the population level, 13 of the 21 gestures we observed were performed predominantly with the right hand. Gestural laterality of signallers was influenced mainly by interactional context, gesture characteristics (except gesture duration) and signallers' hierarchical rank and age. Signallers used their hand ipsilateral to recipients for tactile and visual gestures and their contralateral hand for gestures involving auditory communication and a communication tool. Moreover, signallers' use of their right hand was more important for subordinates. This was also true in negative contexts for gestures common to most of the subjects. Our results further support the hypothesis that laterality in gestural communication might represent a precursor of the left-hemispheric lateralization of language. We discuss our results in relation to theories concerning the origins of cerebral hemispheric lateralization and their consistency with previous studies. Highlights: Chimpanzees are right handed for the most frequent intraspecific gestures considered. Gestural laterality is modulated by several factors and their mutual interactions. The position of interactants and the emotional context influence gestural laterality. Sensory modality, tool use, sharing degree and hierarchy modulate gestural laterality.